Molecular Detection of Toxoplasmosis Using Specific Primers P30, B1, and rDNA - Nurcahyo, Wisnu; Prastowo, Joko; Sahara, Ana (Jurnal Veteriner; Vol 13 No 1 (2012), 2012)
Study in order to develop molecular techniques using specific primers for the early diagnosis oftoxoplasmosis have been conducted. Detection of Toxoplasma gondii genome was performed usingpolymerase chain reaction (PCR) technique. The primers used in this study were rDNA, P30, and B1. ThePCR products were further run using gel electrophoresis (gel 1.5% – 2.0%) and the band was documented.Toxoplasma was detected at 500 bp and 600 bp using primer P30 and B1, respectively. Whereas usingprimer rDNA no band was observed. It was assumed that primer rDNA was not sensitive since the targetamplification was 88 bp.
Keywords: toxoplasma, PCR, specific primer